2022
DOI: 10.1002/adma.202207416
|View full text |Cite
|
Sign up to set email alerts
|

Dense Local Triplet States and Steric Shielding of a Multi‐Resonance TADF Emitter Enable High‐Performance Deep‐Blue OLEDs

Abstract: Multi‐resonance thermally activated delayed fluorescence (MR‐TADF) molecules based on boron and nitrogen atoms are emerging as next‐generation blue emitters for organic light‐emitting diodes (OLEDs) due to their narrow emission spectra and triplet harvesting properties. However, intermolecular aggregation stemming from the planar structure of typical MR‐TADF molecules that leads to concentration quenching and broadened spectra limits the utilization of the full potential of MR‐TADF emitters. Herein, a deep‐blu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…The orientation of optical TDMs of the unsubstituted and YCl3-substituted CsPbI3 NCs was measured by the ratio of horizontal TDMs (Θ). The experimental data are fitted to the pattern simulated employing the classical dipole radiation model [31][32][33][34]. We confirmed that the Θ values of CsPbI3 NCs and YCl3:CsPbI3 NRs film are determined to be 67% and 75% (Figure 6a-b).…”
Section: Resultssupporting
confidence: 66%
“…The orientation of optical TDMs of the unsubstituted and YCl3-substituted CsPbI3 NCs was measured by the ratio of horizontal TDMs (Θ). The experimental data are fitted to the pattern simulated employing the classical dipole radiation model [31][32][33][34]. We confirmed that the Θ values of CsPbI3 NCs and YCl3:CsPbI3 NRs film are determined to be 67% and 75% (Figure 6a-b).…”
Section: Resultssupporting
confidence: 66%
“…Firstly, a moderate dihedral angle between the donor and MR acceptor segments is necessary to guarantee HOMO extension to the bridge-phenyl rings. Secondly, the LE triplet states of the donor and MR acceptor should be energetically close to or higher than CT states to avoid its influence on Δ E ST s 32 . Thirdly, proper substitutions on MR-acceptors should be considered to enhance the MR characters to guarantee the SR-CT excitations on the bridge-phenyl rings.…”
Section: Resultsmentioning
confidence: 99%
“…Organoboron provides a new idea to design optoelectronic materials [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. However, the development of n-type organoboron small-molecular acceptors (OSMAs) with advantages of facile synthesis, synthetic versatility, and simplified purification lags far behind that of their polymer counterparts [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%